James Pennington or James Mill: An Early Correction of Ricardo - Einaudi, Luigi (Quarterly Journal of Economics, 1929)
James Pennington or James Mill: An Early Correction of Ricardo Luigi Einaudi Luigi Einaudi Turin University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 1, November 1929, Pages 164–171, https://doi.org/10.2307/1885445 Published: 01 November 1929